Occupational and residential segregation - Flückiger, Yves, 1955-; Reardon, Sean F.; Silber, Jacques (Emerald, 2009)
This volume is divided into five parts, each one including two chapters. Part I is devoted to 'Information Theory and Segregation Measurement', part II to 'The Gini Index and the Measurement of Segregation', part III to 'Measuring Segregation with Ordered Categories', part IV to 'Exploring Changes in Segregation' and part V to 'Wage Inequality and Segregation'. Let us now review into more details each of these ten chapters.
Keywords: Equality.; Segregation.; elektronické knihy; electronic books